Choledochal cysts. Diagnosis and treatment. Presentation of 6 patients (Colombia Medica, 1986)
Six cases of choledochal cysts, 4 women and 2 males are described during the first and second decades of life. Only in 3 cases the triada of mass, abdominal pain, and jaundice was present. Imaging studies such as ultrasound, CT, isotope scanning, oral cholecystography, and intravenous cholangiography are described, and some were made in these patients. Summaries of the charts, treatments, and surgical techniques are presented.